2021
DOI: 10.1111/ijsa.12341
|View full text |Cite
|
Sign up to set email alerts
|

A good thing takes time: The role of preparation time in asynchronous video interviews

Abstract: Asynchronous video interviews (AVIs) are increasingly used to preselect applicants.Previous research found that interviewees in AVIs receive better interview ratings compared to other forms of interviews. It has been suggested that this difference could be due to the preparation time given for each AVI question. A pilot study confirmed that preparation time in AVIs is indeed beneficial for interview performance. Furthermore, our main study replicated the significant effect of preparation time on interview perf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…For face-toface interviews, we also found that objective questions and a personable interviewer had no impact on honest IM intentions. Even though there is evidence that honest IM can be affected by situational factors (e.g., Basch & Brenner, Melchers, et al, 2021;Bourdage et al, 2018), the results concerning the null effects of warnings are nevertheless in line with previous research that also found only slightly higher honest IM intentions in a verification warning condition compared to a no warning condition (Bill et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…For face-toface interviews, we also found that objective questions and a personable interviewer had no impact on honest IM intentions. Even though there is evidence that honest IM can be affected by situational factors (e.g., Basch & Brenner, Melchers, et al, 2021;Bourdage et al, 2018), the results concerning the null effects of warnings are nevertheless in line with previous research that also found only slightly higher honest IM intentions in a verification warning condition compared to a no warning condition (Bill et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, we note that the evidence base for recommended best‐practice use of AVIs is in its infancy, and we hope that this investigation will provide researchers with context for experimental investigations of the effects of features on applicant reactions and AVI performance. For example, a recent published study by Basch et al (2021) has provided some initial evidence that providing additional preparation time to candidates leads to improved AVI performance. Further, other recent evidence suggests that including rich media content into questions can improve applicant reactions and performance (Saliman & Roulin, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Accordingly, the authors called for researchers to investigate how AVI feature options affect applicant reactions and behaviors. While research into these matters is now emerging (e.g., Basch et al, 2021), we still do not know much about how AVIs are typically designed, nor about which features AVI administrators have adopted and why these features have been adopted. In the absence of benchmarks of the use of AVI design features, it is challenging to estimate the potential impact of any research that seeks to improve AVI design.…”
Section: Introductionmentioning
confidence: 99%
“…For example, enhancing these tools with personalized videos of organizational members and providing candidates with feedback following selection decisions might increase feelings of relatedness. These suggestions need to be empirically tested 202 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%